Bladder cancer - The neglected tumor: A descriptive analysis of publications referenced in MEDLINE and data from the register clinicaltrials.gov - Kunath, Frank; Krause, Steffen F.; Wullich, Bernd; Goebell, Peter; Engehausen, Dirk; Burger, Maximilian; Meerpohl, Joerg J.; Keck, Bastian (BMC Urology, 2013)
Background: Uro-oncological neoplasms have both a high incidence and mortality rate and are therefore a major public health problem. The aim of this study was to evaluate research activity in uro-oncology over the last decade. Methods. We searched MEDLINE and ClinicalTrials.gov systematically for studies on prostatic, urinary bladder, kidney, and testicular neoplasms. The increase in newly published reports per year was analyzed using linear regression. The results are presented with 95% confidence intervals, and a p value <0.05 was considered statistically significant. Results: The number of new publications per year increased significantly for prostatic, kidney and urinary bladder neoplasms (all <0.0001). We identified 1,885 randomized controlled trials (RCTs); also for RCTs, the number of newly published reports increased significantly for prostatic (p = 0.001) and kidney cancer (p = 0.005), but not for bladder (p = 0.09) or testicular (p = 0.44) neoplasms. We identified 3,114 registered uro-oncological studies in ClinicalTrials.gov. However, 85% of these studies are focusing on prostatic (45%) and kidney neoplasms (40%), whereas only 11% were registered for bladder cancers. Conclusions: While the number of publications on uro-oncologic research rises yearly for prostatic and kidney neoplasms, urothelial carcinomas of the bladder seem to be neglected despite their important clinical role. Clinical research on neoplasms of the urothelial bladder must be explicitly addressed and supported. © 2013 Kunath et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2025-08-19
Keywords: Kidney neoplasms; Prostatic neoplasms; Randomized controlled trial; Testicular neoplasms; Urinary bladder neoplasms